Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-03715-9
|View full text |Cite
|
Sign up to set email alerts
|

The associations between infertility-related stress, family adaptability and family cohesion in infertile couples

Abstract: To explore the association between infertility-related stress, family adaptability and family cohesion in infertile couples and the determinants of infertility-related stress in infertile couples. Fertility Problem Inventory (FPI) and Family Adaptability and Cohesion Evaluation Scales (FACESII-CV) were used to measure the infertility-related stress and family adaptability and cohesion of infertile couples. T-test, ANOVA and multiple comparisons (LSD) were conducted to compare the FPI scores of different demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Predisposing factors for infertility included common female/male factors and coronavirus anxiety. In line with these findings, Lei et al (2021) identified low education levels and rural areas as risk factors for infertile men and women experiencing infertility stress [ 47 ]. Another study on infertile women found that the duration of infertility and the relative importance of unknown causes of infertility to other causes of infertility were factors influencing infertile women's stress, but that stress had no significant relationship with education level or age [ 48 ].…”
Section: Discussionmentioning
confidence: 90%
“…Predisposing factors for infertility included common female/male factors and coronavirus anxiety. In line with these findings, Lei et al (2021) identified low education levels and rural areas as risk factors for infertile men and women experiencing infertility stress [ 47 ]. Another study on infertile women found that the duration of infertility and the relative importance of unknown causes of infertility to other causes of infertility were factors influencing infertile women's stress, but that stress had no significant relationship with education level or age [ 48 ].…”
Section: Discussionmentioning
confidence: 90%
“…This result may be caused by excessive intake of fat in the daily diet and lead to an increase in free fatty acids. Large amounts of free fatty acids may have toxic effects on reproductive tissues, causing cellular damage and a chronic low-grade inflammatory state, which can cause infertility [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Items of "infertility is considered as a defect for a woman" and "I feel inferior to others because I cannot get pregnant" are placed in this dimension. Infertility could have mental and social consequences for the individual and could affect the couple's marital relationships [9,19] The item of "I am worry that my husband would remarry or divorce me because I am infertile" is placed in this dimension. There are items in the Fu et al questionnaire about feeling shame and humiliation that are similar to the present questionnaire, but in the present questionnaire self-stigma has gone beyond these feelings and has considered aspects such as getting sad when others have children which is a sign of deep hidden feeling of humiliation; this could be considered as the strength of this instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Women have described infertility as the most saddening experience of their life [9,10]. Motherhood is a part of identity for many women and they would appear more vunerable in the case of infertility in comparison to men and would expereince more stigma [2,11].…”
Section: Introductionmentioning
confidence: 99%